Sub-Saharan Africa at the global education market: role of South Africa - Ramil Ravilevich Asmyatullin (Vestnik RUDN. International Relations, 2016)
This article is dedicated to the development of the higher education in Sub-Saharan countries, particularly to the topic of internationalization of education. Most African countries have underdeveloped education systems. The quality and availability of higher education is a formidable obstacle for economic and social development. There is a growing demand for higher education in the SSA, but national education systems can’t cope fully with it. Hence many students go abroad, mostly in other African countries. The article focuses on the position of South Africa in the global and regional education market. As it’s a regional leader in this field South Africa attracts more than a half of international students within the Sub-Saharan Africa. The main reasons why African students choose South Africa are geographic proximity, familiar culture, lack of wanted higher education programs in their countries. However, there are as well disadvantages like xenophobia and race discrimination. South Africa has become a leader in Africa in the field of higher education, but it plays still small part at a global scale.